Accuracy of the diagnosis of GORD by questionnaire, physicians and a trial of proton pump inhibitor treatment: the Diamond Study. Issue 6 (13th May 2010) - Dent, John; Vakil, Nimish; Jones, Roger; Bytzer, Peter; Schöning, Uwe; Halling, Katarina; Junghard, Ola; Lind, Tore
Abstract : Objective: The aim of this study was to determine the accuracy of the diagnosis of gastro-oesophageal reflux disease (GORD) by the Reflux Disease Questionnaire (RDQ), family practitioners, gastroenterologists and a test of esomeprazole therapy. Methods: This was a single-blind, single-arm study over 3–4 weeks from September 2005 to November 2006. Each symptom-based diagnostic assessment was made blinded to prior diagnoses. Patients were those presenting to their family practitioner with troublesome upper gastrointestinal symptoms (n=308). The RDQ was completed and a symptom-based diagnosis was made by the family practitioner. Placebo esomeprazole was started. Gastroenterologists made a symptom-based diagnosis and then performed endoscopy with 48 h oesophageal pH and symptom association monitoring to determine the presence/absence of GORD. Symptoms were recorded during treatment with 40 mg of esomeprazole for 2 weeks. The main outcome measure was RDQ scoring for the presence of GORD compared with symptom-based diagnosis by family physicians and gastroenterologists. Results: GORD was present in 203/308 (66%) patients. Only 49% of the patients with GORD selected either heartburn or regurgitation as the most troublesome symptom. Sensitivity and specificity, respectively, of the symptom-based diagnosis of GORD, were 62% and 67% for the RDQ, 63% and 63% for family practitioners, and 67% and 70% for gastroenterologists. Symptom response to esomeprazole was neither sensitive nor specific for the diagnosis of GORD. Conclusions: The RDQ, family practitioners and gastroenterologists have moderate and similar accuracy for diagnosis of GORD. Symptom response to a 2 week course of 40 mg of esomeprazole does not add diagnostic precision. Clinical trial number: NCT00291746.